BIN1, myotubularin, and dynamin-2 coordinate t-tubule growth in cardiomyocytes - Perdreau-Dahl, Harmonie; Lipsett, David B.; Frisk, Michael; Kermani, Fatemeh; Carlson, Cathrine R.; Brech, Andreas; Shen, Xin; Bergan-Dahl, Anna; Hou, Yufeng; Tuomainen, Tomi; Tavi, Pasi; Jones, Peter P.; et al. (Circulation research, 2023)
Background: - - Transverse tubules (t-tubules) form gradually in the developing heart, critically enabling maturation of cardiomyocyte Ca2+ homeostasis. The membrane bending and scaffolding protein BIN1 (bridging integrator 1) has been implicated in this process. However, it is unclear which of the various reported BIN1 isoforms are involved, and whether BIN1 function is regulated by its putative binding partners MTM1 (myotubularin), a phosphoinositide 3′-phosphatase, and DNM2 (dynamin-2), a GTPase believed to mediate membrane fission. - - Methods: - - We investigated the roles of BIN1, MTM1, and DNM2 in t-tubule formation in developing mouse cardiomyocytes, and in gene-modified HL-1 and human-induced pluripotent stem cell-derived cardiomyocytes. T-tubules and proteins of interest were imaged by confocal and Airyscan microscopy, and expression patterns were examined by RT-qPCR and Western blotting. Ca2+ release was recorded using Fluo-4. - - Results: - - We observed that in the postnatal mouse heart, BIN1 localizes along Z-lines from early developmental stages, consistent with roles in initial budding and scaffolding of t-tubules. T-tubule proliferation and organization were linked to a progressive and parallel increase in 4 detected BIN1 isoforms. All isoforms were observed to induce tubulation in cardiomyocytes but produced t-tubules with differing geometries. BIN1-induced tubulations contained the L-type Ca2+ channel, were colocalized with caveolin-3 and the ryanodine receptor, and effectively triggered Ca2+ release. BIN1 upregulation during development was paralleled by increasing expression of MTM1. Despite no direct binding between MTM1 and murine cardiac BIN1 isoforms, which lack exon 11, high MTM1 levels were necessary for BIN1-induced tubulation, indicating a central role of phosphoinositide homeostasis. In contrast, the developing heart exhibited declining levels of DNM2. Indeed, we observed that high levels of DNM2 are inhibitory for t-tubule formation, although this protein colocalizes with BIN1 along Z-lines, and binds all 4 isoforms. - - Conclusions: - - These findings indicate that BIN1, MTM1, and DNM2 have balanced and collaborative roles in controlling t-tubule growth in cardiomyocytes.
Veröffentlicht: 4. Mai 2023
Gesehen am 15.08.2023